Macrophage-compatible magnetic achiral nanorobots fabricated by electron beam lithography - Teng Jiang; Xiaoxia Song; Xueliang Mu; U. Kei Cheang (Scientific Reports, 2022)
Abstract With the development and progress of nanotechnology, the prospect of using nanorobots to achieve targeted drug delivery is becoming possible. Although nanorobots can potentially improve nano-drug delivery systems, there remains a significant challenge to fabricating magnetically controllable nanorobots with a size suitable for drug delivery in complex in vivo environments. Most of the current research focused on the preparation and functionalization of microscale and milliscale robots due to the relative difficulties in fabricating nanoscale robots. To address this problem and move towards in vivo applications, this study uses electron beam lithography to fabricate achiral planar L-shaped nanorobots that are biocompatible with immune cells. Their minimal planar geometry enabled nanolithography to fabricate nanorobots with a minimum feature size down to 400 nm. Using an integrated imaging and control system, the locomotive behavior of the L-shaped nanorobots in a fluidic environment was studied by examining their velocity profiles and trajectories. Furthermore, the nanorobots exhibit excellent cell compatibility with various types of cells, including macrophage cells. Finally, the long-term cell culture medium immersion test demonstrated that the L-shaped nanorobots have robust stability. This work will demonstrate the potential to use these nanorobots to operate in vivo without triggering immune cell responses.